Dihydrocaffeic acid improves IL-1β-induced inflammation and cartilage degradation via inhibiting NF-κB and MAPK signalling pathways. Issue 4 (6th April 2023) - Lu, Rui; Wang, Ying-Guang; Qu, Yunkun; Wang, Shan-Xi; Peng, Cheng; You, Hongbo; Zhu, Wentao; Chen, Anmin
Abstract : Aims: Osteoarthritis (OA) is a prevalent joint disorder with inflammatory response and cartilage deterioration as its main features. Dihydrocaffeic acid (DHCA), a bioactive component extracted from natural plant ( gynura bicolor ), has demonstrated anti-inflammatory properties in various diseases. We aimed to explore the chondroprotective effect of DHCA on OA and its potential mechanism. Methods: In vitro, interleukin-1 beta (IL-1β) was used to establish the mice OA chondrocytes. Cell counting kit-8 evaluated chondrocyte viability. Western blotting analyzed the expression levels of collagen II, aggrecan, SOX9, inducible nitric oxide synthase (iNOS), IL-6, matrix metalloproteinases (MMPs: MMP1, MMP3, and MMP13), and signalling molecules associated with nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways. Immunofluorescence analysis assessed the expression of aggrecan, collagen II, MMP13, and p-P65. In vivo, a destabilized medial meniscus (DMM) surgery was used to induce mice OA knee joints. After injection of DHCA or a vehicle into the injured joints, histological staining gauged the severity of cartilage damage. Results: DHCA prevented iNOS and IL-6 from being upregulated by IL-1β. Moreover, the IL-1β-induced upregulation of MMPs could be inhibited by DHCA. Additionally, the administration of DHCA counteracted IL-1β-induced downregulation of aggrecan, collagen II, and SOX9. DHCA protected articular cartilage by blocking the NF-κB and MAPK pathways. Furthermore, DHCA mitigated the destruction of articular cartilage in vivo. Conclusion: We present evidence that DHCA alleviates inflammation and cartilage degradation in OA chondrocytes via suppressing the NF-κB and MAPK pathways, indicating that DHCA may be a potential agent for OA treatment. Cite this article: Bone Joint Res  2023;12(4):259–273.